Influence of Waste Plastic Binder on Sintered Properties of Injection Moulded M2 HSS / Rosniza Rabilah...[et al.] - Rabilah, Rosniza; Budin, Salina; Jaafar, Talib Ria; Hashim, Siti Mardini (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Metal injection molding (MIM) is an effective way for producing small and complex-shape components in high production rates. Selection of binder and its removal in debinding process is a crucial stage in MIM process. In this study, the debinding and sintering characteristics of injection molded M2 HSS using waste plastic binder system has been investigated. The feedstock was formulated with 0.65 volume fraction of molybdenum high speed steel (M2 HSS) with the binders system containing 55wt.% paraffin wax, 35wt.% thermoplastic waste plastic and 10wt.% stearic acid. The moulded parts were immersed in n-heptane at 60°C for 5 hours in order to remove the paraffin wax and stearic acid. The parts were rested in standard low temperature furnace for 2 hours at 52°C to ensure the remaining n-heptane was completely removed and dried. The sintering in vacuum condition occurred at temperature ranges of 1200°C to 1260°C with soaking times of 10 minutes, 30 minutes and 60 minutes. The results showed that the maximum shrinkage of sintered samples was 15% which occurred at sintering temperature of 1260°C. However, the maximum transverse rupture strength (TRS) of 3500 MPa was obtained at temperature of 1240°C and the highest hardness was achieved at sintering temperature of 1220°C with the value of 60.7 HRC. The effects of sintering temperature and soaking time on the physical and mechanical properties are discussed.